Dispersion model of methane (CH4) and carbondioxide (CO2) emissions from punggur landfill batam - ., Yodi; Adicita, Yosef; Rizki Apritama, Muhammad; Wayan Koko Suryawan, I; Prajati, Gita (International Journal of Engineering and Technology, 2019)
One of bad impact from landfill is the increasing of air pollutant level, both in the form of gas and particulates, that is potentially to decrease air quality around landfill area. Dispersion analysis of air pollutant from all resources need to be conducted in order to estimate its bad impacts such as impact to environmental aesthetics, health, and global warming. The common method used is dispersion model of air pollutant. This method estimated quantity of CH4 and CO2 emission with LandGEM application, then calculated the emission of CH4 and CO2 with disperse Gauss equation. Air generated estimated in 2021 by CH4 and CO2 gas total as 2,87x104 Mg/year. The average wind speed in Batam is 6.73 km/hour with atmosfer stability at D condition (very unstable). The highest calculation of CH4 and CO2 concentrations in disperse emission at 123 meters were 0.059g/s and 0.007g/s.Â